SOCIAL PEDAGOGY: PROBLEMS AND SOLUTIONS - Ibodullayeva Zubayda Sherzodovna (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
The exploration of social pedagogy reveals a landscape where education, health, and social welfare intersect, presenting both significant challenges and transformative opportunities. In addressing systemic issues, social pedagogy emphasizes holistic approaches that integrate community engagement and educational frameworks.